Acoustic system for ground truth underwater positioning in DEEC's test tank - Afonso Mateus Bonito (2019)
Development of an acoustic positioning system, capable of estimating, in real time, the three-dimensional position of an object inside the DEEC's test tank. The ability to obtain this ground truth position is fundamental to support tests of underwater navigation systems, and to the control of robotic vehicles such as AUV's and ROV's.